Is there a procoagulant state long-term after lung transplantation? A prospective study. (November 2021) - Sáez-Giménez, Berta; Clofent, David; López Meseguer, Manuel; Bravo Masgoret, Carlos; Monforte, Victor; Berastegui, Cristina; Revilla-Lopez, Eva; Barrecheguren, Miriam; Arjona-Peris, Marta; Ruiz, Victoria; Ramon, Maria Antonia; Gómez-Ollés, Susana; et al.
Abstract: Background: Venous thromboembolism (VTE) is a major complication after lung transplantation (LT). However, its pathophysiology remains unknown, and coagulation profiles have yet to be described. Objective: The aim of this study was to longitudinally assess coagulation status after LT. Methods: We performed a prospective study and described the coagulation profiles of 48 patients at 5 different time-points: before LT and at 24–72 h, 2 weeks, 4 months, and 1 year after LT. Results: At baseline, almost all analyzed coagulation factors were within the normal range, except for FVIII, which was above the normal range. Von Willebrand factor (vWF) and FVIII were increased after LT and remained high at 1 year after transplantation. The cumulative incidence of VTE was 22.9%. Patients who developed VTE had higher FVIII activity 2 weeks after LT. Conclusions: This is the first study to describe coagulation profiles up to 1 year after LT. We show that most markers of a procoagulant state normalize at 2 weeks after LT, but that values of FVIII and vWF remain abnormal at 1 year. This problem has received little attention in the literature. Larger studies are necessary to confirm the results and to design appropriate prophylactic strategies. Highlights: Although Venous thromboembolism is a major complication after lung transplantation, its pathophysiology remains unknown. This is a prospective study to describe the coagulation profiles of 48 patients up to 1 year after LT. This is the first study to describe coagulation profiles up to 1 year after LT. Most markers of a procoagulant state normalize at 2 weeks after LT, but values of FVIII and vWF remain abnormal at 1 year.